Computer-supported cooperative work in Malaysian tourism industry - Abd Aziz, Puteri Noor Ruzanna; Md Tap, Abu Osman; Mahmud , Murni (2013)
Tourism industry is a most vibrant activity in the worldwide. In Malaysia itself the tourism industry is the second largest contributor for Malaysia economy next to the manufacturing sector. The globalization has brings major changes to the growth of technology in human life. The rapid growth of this technology brings new dimension in the tourism industries in Malaysia. By implementing Information Technology (IT) it will encourage the development of this industry and it is very supportive to help rural communities. The need of I.T in tourism industry urges the implementation of CSCW in tourism industry. Its component are very beneficial and in line with the tourism situation.